Efektivitas Program SIPELANDUKILAT dalam Peningkatan Pelayanan Administrasi Kependudukan di Wilayah Pedalaman dan Terpencil: (Studi di Kecamatan Tanjung Palas Timur Kabupaten Bulungan) - Shafri Nur Julianto; Afni Nooraini (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the effectiveness of the SIPELANDUKILAT program (Population Administration Service System for Border and Remote Areas) in improving population administration services in rural and remote areas of Tanjung Palas Timur District, Bulungan Regency, North Kalimantan Province. Using qualitative descriptive methods with an inductive approach, data were collected through interviews with 10 informants, direct observation, and documentation. The theoretical framework employs Siagian's (2011) effectiveness theory, assessed through four dimensions: human resources, funds, facilities and infrastructure; quantity and quality of services; time; and procedures. Findings indicate that the program has not yet reached full effectiveness, particularly due to the absence of specialized training for operators, inadequate facilities and infrastructure, and the transition from the distributed SIAK system to a centralized SIAK system that rendered offline recording equipment unusable. Supporting factors include qualified human resources, assistance from the Provincial Civil Registry Office, and high community participation. The study recommends that Bulungan Regency accelerate adaptation to the centralized SIAK system, improve facilities and infrastructure, and strengthen inter-agency cooperation to optimize population administration services in remote areas.